DISCOURSE OF JOINT PROPERTY IN RIVIEW OF ISTINBATH ISLAMIC LAW - Watni Marpaung; M Amar Adly (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2022)
This paper elaborates the concept of joint property as a unique Islamic legal entity in Indonesia. Positioning the meaning of shared assets with various views of classical fiqh and Indonesianism is a necessity. Even more than that, tracking the legal istinbath method formulated by Indonesian scholars on the concept of joint property is the focus of the article. Positioning the meaning and side of istinbathi ushuly gives strength in the continuity of the implementation of joint property in Indonesia.